2022
DOI: 10.1093/brain/awab291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel nasal oxytocin spray with enhanced bioavailability on autism: a randomized trial

Abstract: Although intranasal oxytocin is expected to be a novel therapy for the core symptoms of autism spectrum disorder, which has currently no approved medication, the efficacy of repeated administrations was inconsistent, suggesting that the optimal dose for a single administration of oxytocin is not optimal for repeated administration. The current double-blind, placebo-controlled, multicentre, crossover trial (ClinicalTrials.gov Identifier: NCT03466671) was aimed to test the effect of TTA-121, a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…All these factors may contribute to the statistically non-significant difference in oxytocin response among different patients with ASD. Moreover, it should be acknowledged that the therapeutic responses to oxytocin treatment for ASD core symptoms may be associated with various treatment factors, such as dosage or dose frequency of oxytocin intervention in different developmental stages, 14 , 30 , 86 , 87 OXTR genetics, 39 and the interactions of dose frequency with OXTR genetics. 33 , 38 Notably, ∼17.47% (80 of 458) of potential oxytocin-related molecular biomarkers and ∼19.72% (156 of 791) of non-PC-OTRGs (Supplemental Table 19) were significantly differentially expressed through modification of histone and/or DNA methylation in ASD cortex compared with that in control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors may contribute to the statistically non-significant difference in oxytocin response among different patients with ASD. Moreover, it should be acknowledged that the therapeutic responses to oxytocin treatment for ASD core symptoms may be associated with various treatment factors, such as dosage or dose frequency of oxytocin intervention in different developmental stages, 14 , 30 , 86 , 87 OXTR genetics, 39 and the interactions of dose frequency with OXTR genetics. 33 , 38 Notably, ∼17.47% (80 of 458) of potential oxytocin-related molecular biomarkers and ∼19.72% (156 of 791) of non-PC-OTRGs (Supplemental Table 19) were significantly differentially expressed through modification of histone and/or DNA methylation in ASD cortex compared with that in control.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Although an increasing number of clinical trials have investigated the efficacy of intranasal oxytocin intervention, the conclusions vary and are controversial. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Certain studies supported the beneficial effects of oxytocin intervention in social functioning and within non-social domains (repetitive behaviour) in patients with ASD, 20 whereas other studies support only one of these effects 19 , 20 , 21 , 22 , 23 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 or neither. 26 , 27 , 34 , 35 Given that these clinical trials employed different experimental designs, inclusion and exclusion criteria for recruiting participants, intervention methods, and approaches for evaluating intervention efficiencies, inconsistencies in the outcomes are inevitable.…”
Section: Introductionmentioning
confidence: 96%
“…In multiple-dose OT trials with individuals with ASD, daily dosing ranged from 8-80 IU and durations from 4 continual days to 24 weeks, but strong empirical support for favoring one dosing scheme over another is currently lacking. Some earlier single-dose trials suggested dose-response curves to exhibit U-shaped forms (Lieberz et al, 2020; Spengler et al, 2017), a notion that is supported by a recent chronic four-week OT administration trial in ASD, identifying a daily total dose of 6 IU of TTA-121 (a new formulation of intranasal OT spray with an enhanced bioavailability) to be the most efficacious one, compared to a lower (3 IU) or higher (10 IU) daily dose (Yamasue et al, 2022). Furthermore, in terms of dosing scheme, recent work showed that intermittent (every other day) administration may be therapeutically more efficient than continual administration to obtain anxiolytic effects and reduce amygdala reactivity (Kou et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…In a separate ongoing study (and so not directly comparable), we have similarly found that 128 μg demonstrates a significant drop in efficacy compared to lower doses that were preventable by the addition of Mg 2+ . Inverted U dose responses have been widely reported for various systems, including social recognition [ 28 ], opioid-induced respiratory depression [ 29 ], and, very recently, in an autism spectrum clinical trial [ 30 ]. Although it is not unknown for peptide neurotransmitters to have an inverted U dose-response, the specific reason for a decrease in withdrawal latency at a higher OT dose is still unclear.…”
Section: Discussionmentioning
confidence: 99%